Research progress on moyamoya disease combined with thyroid diseases - Zhang, Guibo; Liu, Erheng; Tan, XueYi; Liu, Chengyuan; Yang, Shuaifeng (Frontiers in Endocrinology, 2023)
Moyamoya disease(MMD), also known as abnormal cerebral vascular network disease, is characterized by progressive occlusion or stenosis of the internal carotid and cerebral arteries, as well as the formation of an abnormal cerebral vascular network. It is possible to occur worldwide, with more reports from China, Japan, and South Korea. In recent years, there have been more and more reports on the coexistence of thyroid diseases and MMD, but the current explanation for their mechanism is not very clear. This article uses keywords such as "Moyamoya disease", "thyroid", "Grave disease", "thyrotoxicosis", and "thyroid autoimmune antibodies" to search for 52 articles that meet the requirements in medical databases such as PubMed | and Web of Science, reviews the research on the role of thyroid hormone, the mechanism of immune antibodies, possible correlation between thyroid diseases and MMD disease genes, and the treatment methods,discusses the possible relationship between MMD and thyroid diseases in order to provide a reference for the pathogenesis and treatment of MMD with thyroid diseases.